Instytucja dyktatury w Republice Rzymskiej - Rudnicki, Jan (Czasopismo Prawno-Historyczne, 2011)
The dictatorship (magister populi) was an extraordinary magistrate in the Roman Republic, widely used in the period of the classical Republic (4th-3rd century BC). Its origins are subject of serious doubts. One dominant theory sees it as purely republican and Roman invention. According to the second – and more convincing to me – magister populi was at first an ordinary magistrate with the supreme power and later, when the consulate was established, it became an extraordinary office equipped with imperium maius. Dictatorship was an exception from every single major principle of Roman republican constitution. He was not elected by the comitia centuriata, but nominated by the consul earlier authorized by the Senate. In contradiction to other collegial magistrates dictator was a sole performer of his duties. The supreme power of the dictator was limited to the maximum of six months. He was able to control and direct all ordinary magistrates and he was not bound by the rule of incompatibilitas. Finally, his decisions were immune to ius provocationis and ius auxili. During the two centuries of classical Roman Republic the Senate developed many ways to make use of this institution. First and most important was to grant a supreme power to one trusted man in face of a military crisis (rei gerundae causa) or dangerous disturbance in internal affairs (seditionis sedandae causa). Later dictatorship started to be nominated to substitute the consuls not able to conduct their duties both in state or sacral matters (comitiorum habendorum causa, feriarum latiniarum causa). Only once dictatorship was used to perform the duties of a censor (senatus legendi causa). The religious powers of magister populi were performed in case of prodigium by the dictator clavi figendi causa. Contrary to the common, but superficial opinion even the powers of dictator rei gerundae or seditionis sedandae causa were not unlimited. To perform such acts as declaration of war or triumph and even to use the treasury of the Republic, magister populi always needed the approval of the Senate or the Populus. Almost all dictators had nominated the magister equitum as their deputy and “second-incommand”. The master of the horse was assisting the dictator in performing his powers. After the Second Punic War dictatorship in this traditional shape ceased to fit the new reality and became obsolete. It came back to roman constitutional practice in the times of crisis of the Republic. Sulla and later Caesar used it as a form for their absolute power. Caesarian invention of “perpetual dictatorship” proved directly that the idea of old republican dictatorship was rejected. Soon afterwards the dictatorship was abolished and the word “dictator” started to be associated with an autocratic power. In later times many authors stated, that the dictatorship was one of the reasons of the fall of the Republic. This opinion was proved to be superficial and therefore wrong by N. Machiavelli, who analyzed that institution and showed its deeply republican character. From our point of view the roman dictatorship appears to be a prototype of all modern institutions of state of emergency.